Middle Fossa Approach With Anterior Petrosectomy for Resection of a Meningioma Mimicking a Trigeminal Schwannoma, a Step-by-Step Surgical and Anatomical Description: 2-Dimensional Operative Video. Issue 1 (14th February 2019) - Peris-Celda, Maria; Carlstrom, Lucas P; Perry, Avital; Graffeo, Christopher S; Driscoll, Colin L; Link, Michael J
Abstract: Selected upper cerebellopontine angle (CPA)/petroclival region lesions can be visualized and resected through a middle fossa approach with anterior petrosectomy. This approach is particularly well suited for tumors that extend from the CPA into Meckel's cave or the middle cranial fossa. We present the case of a 55-yr-old man who presented with sudden left-sided hearing loss, with complete recovery after medical treatment. MRI demonstrated a left 1.8 cm contrast-enhancing upper CPA lesion with extension into Meckel's cave most consistent with a trigeminal schwannoma. The patient initially opted for observation. MRI 11 mo later showed notable enlargement in the tumor, and the patient started to experience left-sided neuralgic face pain. The decision was made to perform surgery. Documented and verified informed consent was obtained A step-by-step surgical video with surgical anatomy images highlights the 5 steps followed by the authors to perform an anterior petrosectomy. The dura mater was opened parallel to the superior petrosal sinus both in the infratentorial and supratentorial spaces in order to clip and coagulate the superior petrosal sinus and divide the tentorium. The lesion was fully visualized and the trigeminal nerve was clearly identified displaced inferiorly but not splayed by the tumor, making the diagnosis of trigeminal schwannoma unlikely. The lesion was debulked and dissected off the brainstem as well as the trigeminal nerve with the final view of intact nerve fascicles entering the posterior aspect of Meckel's cave. Pathology returned as a WHO grade 1 meningioma. The patient recovered well with only mild facial hypesthesia and complete tumor resection on follow-up imaging.